Where grieving begins building bridges after the Brighton bomb : a memoir - Magee, Patrick 1951- (Pluto Press, 2021)
The memoir of the 'Brighton Bomber', Patrick Magee
Includes index
Keywords: Magee, Patrick -- 1951-; Geschichte 1984; Sprengstoffanschlag; Nordirlandkonflikt; Brighton; Magee, Patrick / 1951-; Terrorists / Northern Ireland / Biography; Northern Ireland / History / 1968-1998; Autobiografie